1994
DOI: 10.1002/ijc.2910560408
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical localization of matrix metallloproteinase 2 and its specific inhibitor timp‐2 in neoplastic tissues with monclonal antibodies

Abstract: Matrix metalloproteinase-2 (MMP-2), synthesized as a 631 amino-acid proenzyme, is activated by cleavage of the first 80 amino acids and naturally inhibited by tissue inhibitor of metalloproteinase-2 (TIMP-2). We report here the production of MAbs against MMP-2 and TIMP-2 and their use in localizing the respective antigens on tumor tissues. The anti-MMP-2 MAb recognized the latent and activated MMP-2 mutant protein (mutein) with C-terminal deletion at amino acid 425, indicating that both N- and C-terminal amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
61
1

Year Published

1997
1997
1999
1999

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 12 publications
13
61
1
Order By: Relevance
“…The TIMP-2 positivity was most prominent in the tumour stroma, a finding also reported by others (Poulsom et al, 1992;Urbanski et al, 1993;Hoyhtya et al, 1994). Studies on the closely related TIMP-1 have shown similar distribution, predominantly to the ECM of colorectal tumours (Hewitt et al, 1991;Newell et al, 1994;Kossakowska et al, 1996), but we are not aware of any studies exploring the relation between TIMP-1 expression and tumour staging and survival in colorectal cancer.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The TIMP-2 positivity was most prominent in the tumour stroma, a finding also reported by others (Poulsom et al, 1992;Urbanski et al, 1993;Hoyhtya et al, 1994). Studies on the closely related TIMP-1 have shown similar distribution, predominantly to the ECM of colorectal tumours (Hewitt et al, 1991;Newell et al, 1994;Kossakowska et al, 1996), but we are not aware of any studies exploring the relation between TIMP-1 expression and tumour staging and survival in colorectal cancer.…”
Section: Discussionsupporting
confidence: 74%
“…We found weak focal or weak diffuse epithelial TIMP-2 staining in as many as 93 (44%) out of the 212 tumours, while Hoyhtya et al (1994) observed strong cytoplasmic staining in 22% of tumour epithelium but, as the clinicopathological variables in these patient materials are possibly not identical, no conclusions may be drawn.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations